Distribution of Sipuncula in the Gulf of Valencia and Cape Nao (western Mediterranean) - Ferrero-Vicente, L. M.; De-La-Ossa-Carretero, J. A.; Del-Pilar-Ruso, Y.; Sánchez-Lizaso, J. L. (Zootaxa, 2013)
The present study analyses the distribution and diversity of sipunculan species inhabiting soft substrata in the Gulf of Va-lencia and Cape Nao (western Mediterranean) in relation to the characteristics of the sediment. Eighty-seven stations in 14 localities were sampled annually from 2004 to 2008. Nine species were reported, with Aspidosiphon (Aspidosiphon) muelleri being the dominant species in the area and Thysanocardia procera the most widely distributed. Pearson correla-tion coefficient and multivariate analysis showed how sipunculan abundances of certain species were related to the sedi-ment characteristics, especially grain size. The shell-dwelling species A. (A.) muelleri and Phascolion (Phascolion) caupo were dominant in stations with high amount of coarse sand and gravel, while Sipunculus (Sipunculus) nudus appeared in stations dominated by fine sand with low organic content. Pn. (Pn.) caupo and T. procera were reported for the first time in the study area. Moreover, it was the second record of Pn. (Pn.) caupo for the Mediterranean Sea.